Long-Term Weight Trajectory and Risk of Hip Fracture, Falls, Impaired Physical Function, and Death - LeBlanc, Erin S. (J Am Geriatr Soc, 2018)
BACKGROUND/ OBJECTIVES: Determine the association of weight trajectories with health status and mortality in older women. DESIGN: Cohort study SETTING: Study of Osteoporotic Fractures (US). PARTICIPANTS: 1,323 older, community-dwelling women (mean baseline [1986–88] age of 68 [65–81] and 20-year exam age [2006–2008] of 88 [83–102]), with follow-up through 2016. MEASUREMENTS: Body weight measured repeatedly over 20 years (mean 8 weights). Logistic and Cox proportional hazard models were used to evaluate whether 20-year weight trajectory measures were associated with hip fracture, falls, physical performance, and/or mortality. Voluntary and involuntary weight loss could not be distinguished. RESULTS: In models adjusted for age, clinic, calcium use, Year 20 weight, walking speed, comorbidity score, smoking, self-reported health, and walking for exercise, women with moderate weight loss (>9.0 kg) over 20 years had a 74% increased risk of death (HR=1.74 [95% CI: 1.37, 2.20]) in the 5 years after the Year 20 visit compared to those with no weight loss. They also had a greater than 2-fold increased risk of suffering a hip fracture (HR=2.56 [95% CI: 1.39, 4.70]). They were 3.6 times (OR=3.60 [95% CI: 1.86, 6.95]) more likely to have poor physical function at the Year 20 visit than women with no weight loss. However, there was no increased risk of 2 or more falls in the 1.5 years after the Year 20 visit. Weight variability and abrupt weight decline were not associated with adverse health oucomes (falls, fractures, and mortality), but those in the highest quartile of variability were 2.3 times (OR=2.26 [95% CI: 1.34, 3.80]) more likely to have poor physical function scores. CONCLUSIONS: In women surviving past 80 years of age, moderate weight loss over 20 years was associated with an increased risk of hip fracture, poor physical function, and mortality, but without an apparent increase in falls. Future work should separate voluntary from involuntary weight loss.